Algorithm of route discovery based on distance prediction in MANET - LI Shi-bao; HONG Li (Tongxin xuebao)
A scheme of route discovery was provided based on the distance prediction to destination.Hops table was established to store historical records.The long-range information and instantaneous information were extracted from historical records.The distance to the destination was calculated by weight sum of both long-range information and instantaneous information.By aid of the distance predicted,the optimized parameters of ERS including the initial TTL value,broadcast threshold and step size of ERS were calculated.Simulation results showed that the new scheme significantly improved performance of the protocol under many kinds of simulation scenarios.The routing overhead was saved and the end-to-end delay of the packet was reduced.At the same time,the new scheme was also easy to implement.